The Relationship Between Work-Family Conflict and Role Overload with Burnout in Working Mothers at Private Companies in Bandung Regency - Annisa Intan Puspitasari; Rifqi Farisan Akbar (Training & Research Institute - Jeramba Ilmu Sukses, 2026)
This study investigates the association between work–family conflict, role overload, and burnout among working mothers employed in private-sector organizations in Bandung Regency. A quantitative correlational design was implemented, involving 100 respondents selected via probability sampling using the Slovin formula. Data were collected using an online questionnaire that incorporated established instruments adapted to the research context, including measures of work–family conflict, role overload, and burnout. Statistical analysis was conducted using IBM SPSS Statistics after the data met the required analytical assumptions. The results indicate that work–family conflict shows a very strong relationship with burnout, reflected by a correlation coefficient of r = 0.932 (p < 0.001). Role overload also demonstrates a strong association with burnout, with a correlation value of r = 0.855 (p < 0.001). Furthermore, when examined simultaneously, both variables contribute significantly to burnout, as evidenced by an F value of 338.507 (p < 0.001) and a coefficient of determination (R²) of 0.875. This finding suggests that 87.5% of the variance in burnout among working mothers can be explained by the combined influence of work–family conflict and role overload. Overall, the findings highlight that competing role demands and excessive workload pressures substantially increase vulnerability to burnout. These results underscore the importance of organizational strategies that emphasize workload balance, role clarity, and supportive work policies to mitigate burnout risks among working mothers.